EFL Learning Strategies of Indonesian University Students for Academic Writing Skills: A Systematic Literature Review - Nadhifah, Siti; Khafshoh, Adira Lizaria; Suryati, Nunung (Jurnal Pendidikan Humaniora, 2023)
Academic writing is a crucial skill for Indonesian university students, significantly influencing their EFL learning performance. This systematic literature review aims to examine the diverse learning strategies employed by these students to enhance their academic writing skills and reveal the predominant strategy employed by the students. Combining systematic literature review and thematic analysis, this study reveals five categories for academic writing strategies, those are metacognitive, cognitive, social, affective, and compensation strategies. This study highlights a predominant use of metacognitive strategies, comprising 36% of the strategies identified. This emphasis underscores students' commitment to higher-order thinking during the writing process and highlights the importance of metacognition in effective language learning. The distribution of cognitive, social, affective, and compensation strategies illustrates a multifaceted approach to academic writing. The findings emphasize the adaptability of EFL university students in Indonesia in addressing academic writing challenges through various strategies, thereby promoting a comprehensive learning environment. This study recommends further investigation into cultural and contextual factors influencing strategy selection, providing educators with insights for tailored instructional practices.